(untitled) (Research, Society and Development, 2021)
The nature of the fatty acid presented in each type of vegetable oil will determine the oil’s characteristic. The purpose of this review is to describe the medium chain fatty acids present in vegetable oils absorption mechanism and their benefits for human body, combined with technological advantages in the preparation of food formulations. Highlighting how the source of the raw material and the extraction method interfere with the concentration of fatty acids present in the oils. It is a review of narrative literature, which used as a theoretical framework recent scientific articles in the English language. Oils derived from coconut, palm kernel, and babassu, for example, have a solid or semi-solid characteristic at room temperature. This happens due to the presence of saturated fatty acids with medium-length carbon chains, that is from 6 to 12 carbons. Although medium-chain fatty acids are saturated, they present characteristics that are different from other long-chain saturated fatty acids. They are quickly digested by the body, which favors the absorption and the using of these nutrients, leading an impact on diseases’ control, such as obesity, diabetes and hypertension. In addition, due to their chemical structure, medium chain fatty acids can be used in the food industry as a substitute for animal fat, combining their nutritional benefits with technological advantage, being used in food preparations to impact texture, flavor, stabilize emulsions, and improve the rheological characteristics of the product.